Inhalable Dust Measurements as a First Approach to Assessing Occupational Exposure in the Pharmaceutical Industry - Champmartin, C.; Clerc, F. (Journal of occupational and environmental hygiene, 2014)
Occupational exposure to active ingredients in the pharmaceutical industry has been the subject of very few published studies. Nevertheless, operations involving active powdered drugs or dusty operations potentially lead to operator exposure. The aim of this study was to collect occupational exposure data in the pharmaceutical industry for production processes involving powdered active ingredients. While the possibility of assessing drug exposure from dust level is examined, this article focuses on inhalable dust exposure, without taking chemical risk into account. A total of 377 atmospheric (ambient and personal) samples were collected in nine drug production sites (pharmaceutical companies and contract manufacturing organizations) and the dust levels were assessed. For each sample, relevant contextual information was collected. A wide range of results was observed, both site- and operation-dependent. Exposure to inhalable dust levels varied from 0.01 mg/m 3 to 135 mg/m 3 . Though restricted to dust exposure, the study highlighted some potentially critical situations or operations, in particular manual tasks (loading, unloading, mechanical actions) performed in open systems. Simple preventive measures such as ventilation, containment, and minimization of manual handling should reduce dust emissions and workers' exposure to inhalable dust.